Directions for educational development in the Year of the Teacher and Tutor - Veriaskina A. N., Sabodina E. P., Dzokaeva Z. M., Pokhilko A. D., Gubanova M. A., Sian I., Vlasova S. A., Dormidontov R. A., Omarov O. M., Ismailov S. O., Annaev R. I., Narykova O. N., Liakhova E. G., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Petrova N. G., Pogosian S. G., Zaritskaia V. V., Koreneva A. V., Ryzhkova I. V., Denisova O. A., Lekhanova O. L., Gudina T. V., Glukhova O. A., Bukin D. A., Zinin S. V., Tkachenko I. S., Panteleeva N. G. (Directions for educational development in the Year of the Teacher and Tutor, 2023)
the issue of learning motivation is one of the most important in psychology and pedagogy. The importance of this issue is determined by the fact that the motivation of learning is a decisive factor in the effectiveness of the educational process. Formation of interest in learning is the result of the whole educational process at school. Despite the improvement of the teaching system, the use of methods of problem and developmental learning, the accumulated experience and materials on the formation of motives for learning activities of schoolchildren, there is a difficulty in the effective formation of interests in learning, especially among adolescents. The chapter reflects the issues of motivation of modern schoolchildren and students of secondary professional institutions. The author has made an attempt to analyze the problems on the basis of the study of questionnaires of three adolescent groups. The factors influencing motivation through the perspective of peculiarities of adolescence are analyzed.
Keywords: образование; мотивация; профессиональная деятельность; motivation; познавательный интерес; education; professional activity; cognitive interest